ANALYSIS OF THE INFLUENCE OF RELATIONSHIP TERMINATION COST, ORGANIZATIONAL COOPERATION ON THE ADAPTATION OF NEW HABITS IN THE PANDEMIC - Cahya Purnama Asri (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study examines the Analysis of the Effect of the Relationship Termination Cost, Organizational Cooperation on the Adaptation of New Habits during the Covid 19 Pandemic. This research was conducted on the Industry in Yogyakarta, the sample used in this study was 80, and the analytical tool used was SPSS software as the tool. Is there a positive influence between Relationship Termination Cost on adaptation, is there a positive influence Relationship Termination Cost on organizational cooperation, is there a positive influence between Relationship Termination Cost on adaptation through organizational collaboration as a mediator in the industry in Yogyakarta